2022
DOI: 10.1186/s12935-022-02804-7
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid: a natural modulator of signaling networks in different cancers

Abstract: Incidence rate of cancer is estimated to increase by 40% in 2030. Furthermore, the development of resistance against currently available treatment strategies has contributed to the cancer-associated mortality. Scientists are now looking for the solutions that could help prevent the disease occurrence and could provide a pain-free treatment alternative for cancers. Therefore, efforts are now put to find a potent natural compound that could sever this purpose. Ursolic acid (UA), a triterpene acid, has potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 142 publications
0
18
0
Order By: Relevance
“…Thus, it is possible that in PCa cells, disruption of AR signaling through inhibition of RORγ is the primary MOA of UA. UA has been shown to display anti-growth effects in cells of different cancers, including prostate cancer, breast cancer, lung cancer, colorectal cancer, and pancreatic cancer (Khwaza et al, 2020;Zafar et al, 2022). However, the direct target of UA in cancer cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible that in PCa cells, disruption of AR signaling through inhibition of RORγ is the primary MOA of UA. UA has been shown to display anti-growth effects in cells of different cancers, including prostate cancer, breast cancer, lung cancer, colorectal cancer, and pancreatic cancer (Khwaza et al, 2020;Zafar et al, 2022). However, the direct target of UA in cancer cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These data together strongly suggested that the effects by UA treatment on AR expression and signaling is likely through its inhibition of RORγ function in the PCa cells. Several studies showed that UA can inhibit cancer cell and tumor growth by interfering with cell cycle, proliferation, apoptosis, inflammation, angiogenesis, and metastasis ( Iqbal et al, 2018 ; Kornel et al, 2022 ; Zafar et al, 2022 ). However, there has been no evidence showing that UA can affect AR expression and/or AR signaling, which is the key driver of PCa development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…For instanced, the ursolic acid, a natural triterpene acid, has potential to inhibit the tumor progression involved in inhibition of Akt, mToR, and ERK. [164] Belamchinenin A (138), an unprecedented 6/5/6 fused tricyclic triterpenoid with a novel carbon skeleton, has been isolated from the rhizomes of Belamcanda chinensis. [160] The absolute configuration of tricyclic nucleus system has been unequivocally assigned by ECD calculation.…”
Section: Triterpenoidsmentioning
confidence: 99%
“…For instanced, the ursolic acid, a natural triterpene acid, has potential to inhibit the tumor progression involved in inhibition of Akt, mToR, and ERK. [ 164 ]…”
Section: Triterpenoidsmentioning
confidence: 99%
“…Cancer is considered a versatile and therapeutically challenging disease, and rapidly evolving pre‐clinical and clinical investigations have started to focus on the molecular mechanisms that trigger cancer initiation and progression [1] . The World Health Organization (WHO) estimated that about 10 million deaths and 1.8 million new cancer cases would have occurred worldwide in 2020 [2] . In 2030, the global cancer death toll is projected to rise by 75 %, with middle‐ and low‐income countries being most affected.…”
Section: Introductionmentioning
confidence: 99%